2009
DOI: 10.1016/j.apm.2007.11.023
|View full text |Cite
|
Sign up to set email alerts
|

New stochastic model for dispersion in heterogeneous porous media: 1. Application to unbounded domains

Abstract: A new model of solute dispersion in porous media that avoids Fickian assumptions and that can be applied to variable drift velocities as in non-homogeneous or geometrically constricted aquifers, is presented. A key feature is the recognition that because drift velocity acts as a driving coefficient in the kinematical equation that describes random fluid displacements at the pore scale, the use of Ito calculus and related tools from stochastic differential equation theory (SPDE) is required to properly model in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(23 citation statements)
references
References 42 publications
3
20
0
Order By: Relevance
“…The previous article [15] showed that the stochastic dispersion model gives diffusive dispersion (with a constant dispersivity) for a constant drift velocity, in agreement with the advection-dispersion equation (ADE). On the other hand, when the drift velocity increases or decreases linearly, a time-dependent dispersivity was found.…”
Section: Introductionmentioning
confidence: 51%
See 4 more Smart Citations
“…The previous article [15] showed that the stochastic dispersion model gives diffusive dispersion (with a constant dispersivity) for a constant drift velocity, in agreement with the advection-dispersion equation (ADE). On the other hand, when the drift velocity increases or decreases linearly, a time-dependent dispersivity was found.…”
Section: Introductionmentioning
confidence: 51%
“…The quantity X n (t) defined above is a generalisation of the peak position X(t) previously encountered in [15]. Introducing the abbreviated notation 1-33 for Eq.…”
Section: Advection In Piecewise Drift Velocity Fieldsmentioning
confidence: 99%
See 3 more Smart Citations